1992
DOI: 10.1002/ijc.2910510403
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus (HPV) infection, hiv infection and cervical cancer in Tanzania, East Africa

Abstract: The presence of HPV-DNA was determined in tumor biopsies of cervical-cancer patients and in cervical swabs of non-cancer patients from Tanzania, East Africa, by Southern blot hybridization and/or PCR. HPV types 16 and 18 were detected in 38% and 32%, respectively, of 50 cervical-carcinoma biopsies. A consensus primer PCR capable of detecting a broad spectrum of HPV types revealed the presence of HPV-DNA in 59% of 359 cervical swabs of non-cancer patients. Type-specific PCR showed that types 16 and 18 accounted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
74
1
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 24 publications
13
74
1
1
Order By: Relevance
“…However most of subjects with SIL (88.9%) were significantly detected among HIV seropositive women. These results are consistent with other study reports elsewhere (Massad 1999;Moodley et al, 2006;Parham et al, 2006), however they differ from those reported in the study done in Dar es Salaam, Tanzania which showed that HIV serostatus was not significantly associated with SIL (Meulen et al 1992). This could have happened due to a number of reasons.…”
Section: Discussionsupporting
confidence: 85%
“…However most of subjects with SIL (88.9%) were significantly detected among HIV seropositive women. These results are consistent with other study reports elsewhere (Massad 1999;Moodley et al, 2006;Parham et al, 2006), however they differ from those reported in the study done in Dar es Salaam, Tanzania which showed that HIV serostatus was not significantly associated with SIL (Meulen et al 1992). This could have happened due to a number of reasons.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have reported a high prevalence of multiple HPV infections among HIV-infected women (Palefsky et al, 1999;Gravitt et al, 2002) which is associated with an increased risk of intraepithelial neoplasia and of cancer (Moscicki et al, 2004a;Herrero et al, 2005). As was found in other African studies (Ter Meulen et al, 1992;Chabaud et al, 1996;La Ruche et al, 1998;Bayo et al, 2002;Kay et al, 2003), HPV-16 and -18 were less common than other HR-HPV types overall, but they were involved in 64% of HSIL lesions, while 93% of women with HSIL had viruses related to the HPV-16 or HPV-18 phylogenetic groups. Therefore, administration of a bivalent HPV-16/18 vaccine in this population before they get exposed might have the potential to prevent the majority of highgrade lesions in this population, but this would need to be determined in prospective studies.…”
Section: Discussionsupporting
confidence: 52%
“…1 The incidence of infection with either high-or low-risk HPV types in the female population of East and Central Africa, as elsewhere, reaches 40 -90%. [1][2][3][4] Notwithstanding that high number, only relatively few women will develop the cancer.…”
mentioning
confidence: 99%